Prevalence of Suicidal Ideation among Pregnant Women in Gran Canaria - María del Amor Santana-González; María Granada Vázquez-Núñez; Mar Miranda-Sánchez; Héctor González-de la Torre; Jesús María González-Martín; Julia Jeppesen-Gutiérrez; Iraya Monagas-Agrelo (Women, 2023)
Suicidal ideation represents a significant predictor of completed suicide. Recent research indicates that it is the leading cause of maternal mortality during pregnancy in industrialized countries, as well as in the 12 months following childbirth, with prevalence rates among pregnant women ranging from 3% to 33%. This study aimed to estimate the prevalence of suicidal ideation among pregnant women in Gran Canaria. A cross-sectional, descriptive, and observational study was conducted at the University Hospital Complex Insular Materno-Infantil of Gran Canaria (CHUIMI). Consecutive non-probabilistic sampling was employed among pregnant women in their 20th to 22nd week of pregnancy. Participants completed the PHQ-9 questionnaire, the Paykel Scale, and a sociodemographic questionnaire to assess associated risk factors. A total of 9.57% of pregnant women reported experiencing some level of suicidal ideation. Factors that increased the risk of suicidal ideation included employment status (p-value = 0.031), prior abortions/miscarriages (p-value < 0.001), educational level (p-value = 0.005), and having living children (p-value = 0.018). This study suggests that the prevalence of suicidal ideation among pregnant women in Gran Canaria may be higher than previously reported in the literature. Therefore, early identification of suicidal ideation is crucial for timely intervention.